2016
DOI: 10.1186/s13045-016-0345-3
|View full text |Cite
|
Sign up to set email alerts
|

T cells in multiple myeloma display features of exhaustion and senescence at the tumor site

Abstract: BackgroundMultiple myeloma is an incurable plasma cell malignancy that is mostly restricted to the bone marrow. Cancer-induced dysfunction of cytotoxic T cells at the tumor site may be responsible for immune evasion and therapeutical failure of immunotherapies. Therefore, enhanced knowledge about the actual status of T cells in myeloma bone marrow is urgently needed. Here, we assessed the expression of inhibitory molecules PD-1, CTLA-4, 2B4, CD160, senescence marker CD57, and CD28 on T cells of naive and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
224
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(245 citation statements)
references
References 55 publications
15
224
2
4
Order By: Relevance
“…Manual gating of SIRIUS WB samples showed that there was a significant increase in granzyme B production among responders to daratumumab. This is important to note, given that recent studies have spoken to the varied functional status of both peripheral blood and BM T cells from multiple myeloma patients (40,41). Moreover, these findings align with work conducted by Chatterjee et al, which showed that inhibition of CD38 increased NAD + -dependent activity of Sirt1 and enhanced the anti-tumor effect of CD8 + T cells (42).…”
Section: Discussionsupporting
confidence: 85%
“…Manual gating of SIRIUS WB samples showed that there was a significant increase in granzyme B production among responders to daratumumab. This is important to note, given that recent studies have spoken to the varied functional status of both peripheral blood and BM T cells from multiple myeloma patients (40,41). Moreover, these findings align with work conducted by Chatterjee et al, which showed that inhibition of CD38 increased NAD + -dependent activity of Sirt1 and enhanced the anti-tumor effect of CD8 + T cells (42).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, immune dysfunction in MM also involves dysregulation of T cells and the innate immune system which we were not able to evaluate in the current study. [35][36][37][38][39][40] In conclusion, in our population-based study on 2557 cases of newly diagnosed symptomatic MM, we have identified ISS score of II or II, high LDH and renal impairment as specific risk factors for the development of pneumonia and/or sepsis within 6 months from diagnosis. We could not find clinical important association between immunoparesis and risk of pneumonia or sepsis.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, we have only included infections that occurred during the first 6 months from MM diagnosis; however, it is reasonable to assume that the degree of immunoparesis changes over time and that the risk factors for infections might be different later in the disease stage. Finally, immune dysfunction in MM also involves dysregulation of T cells and the innate immune system which we were not able to evaluate in the current study …”
Section: Discussionmentioning
confidence: 78%
“…Exhausted T cells expressing immune checkpoint receptors are involved in disease progression in cancer models, although the role of exhausted T cells in the pathophysiology of MM remains controversial [15,80,81]. An in vivo murine myeloma model demonstrated that the expression levels of immune checkpoint receptors such as programmed cell death protein 1 (PD-1), T-cell immunoglobulin and ITIM domains (TIGIT), lymphocyte activation gene-3 (LAG-3), and T-cell immunoglobulin mucin-3 (Tim-3) were increased on CD8 + T cells in bone marrow in MM-relapsed mice compared with those in control mice and MM-controlled mice [82].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%